RETRACTED: Environmental Impact of Pharmaceutical Pollutants: Synergistic Toxicity of Ivermectin and Cypermethrin - Davide Di Paola; Carmelo Iaria; Fabio Marino; Enrico Gugliandolo; Cristian Piras; Rosalia Crupi; Salvatore Cuzzocrea; Nunziacarla Spanò; Domenico Britti; Alessio Filippo Peritore (Toxics)
Veterinary antiparasitic pharmaceuticals as well as pesticides have been detected in surface waters, and they may cause several toxic effects in this environmental compartment. In the present study, we evaluated the toxicity after exposure of different concentration of ivermectin (IVM; 50, 100, and 200 μg L−1) and cypermethrin (CYP; 5, 10, and 25 μg L−1) and the combination of these two compounds at non-toxic concentration (IVM 100 + CYP 5 μg L−1) in zebrafish embryos. Combination of IVM at 100 μg L−1 with CYP at 5 μg L−1 exposure induced hatching delay and malformations at 96 hpf in zebrafish larvae as well as significant induction of cell death in zebrafish larvae. At the same time, the two single concentrations of IVM and CYP did not show a toxic effect on zebrafish development. In conclusion, our study suggests that IVM and CYP show a synergistic effect at common, ineffective concentrations, promoting malformation and cell death in fish development.